A novel high-precision ground-based aircraft landing system capitalizing on towers trilateration - Salih, Ahmad Abbas Al-Ameen (2013)
The rapid increase in aviation industry requires parallel effective plans, programs and designs of systems and facilities nationwide to fulfill the increasing needs for safe air transportation. Aircraft landing remains a problem for a long time all over the world. Systems that aircrafts rely on in landing are unreliable to perform a precise guidance due to many limitations such as inaccuracy, unreliability and dependency. In low visibility conditions, when pilots are unable to see the runway, the aircrafts are diverted to another airport. However, low visibility can also affect all airports in the vicinity, forcing aircrafts to land in low visibility conditions depending on Instrument Flight Rules (IFR). Aircraft approach and landing are the most hazardous portions of flight; accidents records indicate that, approximately 50 percent of the accidents occur during aircraft landing. International Civil Aviation Organization (ICAO) has divided landing systems into three categories according to decision height, visibility and runway visual range. Category IIIB is currently the best available system. It requires a runway visual range not less than 50 meter. Category IIIC is not yet in operation anywhere in the world. It requires landing in zero visibility. Nevertheless, the accuracy of existing aircraft landing systems has not been able to match ICAO required standards for landing blindly in bad weather conditions. Air navigation involves the processes of monitoring and controlling the movement of aircraft from takeoff to landing. Currently, Global Positioning System (GPS) is the main navigation system used all over the world for aircraft navigation, approach and landing. However, in aircraft approach and landing phase, the accuracy of GPS is not sufficient to perform a perfect landing due to the possibility of aircraft to be drifted out of the runway. The accuracy of GPS could be improved by sending correction messages from ground and satellite based stations. However, improved accuracy has not been able to meet ICAO standards for blind landing. In this thesis, aircraft landing systems characteristics, performances and accuracies have been studied and compared for the purpose of assessing limitations and drawbacks. A Ground-based Aircraft Landing System capitalizing on concept of trilateration has been proposed to meet ICAO standards for all-weathers to perform aircraft precision approach and landing. System specifications have been calculated, designed and then simulated using MATLAB. A simulated design has been performed using MATLAB Simulink to simulate transmission and reception of data for accurate aircraft positioning and precise guidance to runway touch point. Aircraft positioning simulations have been performed comparing the proposed system accuracy with current aircraft landing systems. The accuracy of the proposed system has been found equipment dependent. It was calculated for different equipment specifications and was found in sub-meter level. A further accuracy improvement could be obtained by the use of better equipment performance in mitigating multipath and receiver noise. In conclusion, this system provides a solution for aircraft landing in all-weathers and low visibility conditions with high precision guidance. For an easy access and simple indication of aircraft approaching the runway, ILS style indicator has been attached to indicate the aircraft position with respect to reference path and runway touch point. The indicator has been simulated using VisualBasic.net to provide an accurate aircraft deviation from recommended route points coordinates enhancing the aircraft to land in all weather conditions regardless of level of visibility and runway visual range. The calculation and simulation of system performance demonstrated the feasibility of the system to blindly guide the aircraft to runway touch point with high precision in all-weather conditions.